Modeling Evidence-Based Application: Using Team-Based Learning to Increase Higher Order Thinking in Nursing Research - Bridget Moore; Jennifer Styron; Kristina Miller (Journal of Systemics, Cybernetics and Informatics, 2015)

(untitled)
Nursing practice is comprised of knowledge, theory, and research [1]. Because of its impact on the profession, the appraisal of research evidence is critically important. Future nursing professionals must be introduced to the purpose and utility of nursing research, as early exposure provides an opportunity to embed evidence-based practice (EBP) into clinical experiences. The AACN requires baccalaureate education to include an understanding of the research process to integrate reliable evidence to inform practice and enhance clinical judgments [1]. Although the importance of these knowledge competencies are evident to healthcare administrators and nursing leaders within the field, undergraduate students at the institution under study sometimes have difficulty understanding the relevance of nursing research to the baccalaureate prepared nurse, and struggle to grasp advanced concepts of qualitative and quantitative research design and methodologies. As undergraduate nursing students generally have not demonstrated an understanding of the relationship between theoretical concepts found within the undergraduate nursing curriculum and the practical application of these concepts in the clinical setting, the research team decided to adopt an effective pedagogical active learning strategy, team-based learning (TBL). Team-based learning shifts the traditional course design to focus on higher thinking skills to integrate desired knowledge [2]. The purpose of this paper is to discuss the impact of course design with the integration of TBL in an undergraduate nursing research course on increasing higher order thinking. [1] American Association of Colleges of Nursing, The Essentials of Baccalaureate Education for Professional Nursing Practice, Washington, DC: American Association of Colleges of Nursing, 2008. [2] B. Bloom, Taxonomy of Educational Objectives, Handbook I: Cognitive Domain, New York: McKay, 1956.